1974
DOI: 10.1021/i260051a019
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Reactor Wall in the Thermal Hydrocracking of Polyaromatic Compounds

Abstract: With spargers of small orifice, water, acetone, and carbon tetrachloride display a laminar regime (with discrete bubbles). Only with water, however, is there a large laminar region. With all other liquids the gas flow was completely in turbulent flow a t superficial gas velocities above 4 ft/min.Of the liquid physical properties of density, surface tension, and viscosity, only density showed a significant effect on back-mixing and only in the 0.75-in. tube. The effect in the 1.8-in. tube was almost negligible.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1975
1975
1988
1988

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Preliminary results indicate some difficulties with carbon balances, since up to 20% of the carbon is unaccounted for at lower temperatures. The extent of cracking in the tube is unknown, although it appears to be significant based on the carbon balances and previous measurements (Gentry, 1928b;Brooks, 1966;Slotboom and Penninger, 1974). Finally, the acquisition of kinetic data would appear to be difficult.…”
Section: Captive Sample Techniquesmentioning
confidence: 99%
“…Preliminary results indicate some difficulties with carbon balances, since up to 20% of the carbon is unaccounted for at lower temperatures. The extent of cracking in the tube is unknown, although it appears to be significant based on the carbon balances and previous measurements (Gentry, 1928b;Brooks, 1966;Slotboom and Penninger, 1974). Finally, the acquisition of kinetic data would appear to be difficult.…”
Section: Captive Sample Techniquesmentioning
confidence: 99%
“…The migration of metal particles on top of the growing carbon leads to catalytic coke formation. However, if these metal particles become encapsulated by carbon the formation of catalytic coke ceases resulting in a constant coking rate (Slotboom and Penninger, 1974;Trimm, 1977). Albright and Yu (1978) reported that relatively high levels of metal sulphides promote the formation of inactive coke containing no metal granules.…”
mentioning
confidence: 99%
“…Maybe a definite solution to the problem can be found in an effect which has not yet been considered in the preceding discussion, namely, the participation of the reactor wall. Extensive experimental work which was reported elsewhere [13] found that the hydrocracking does not proceed without an "active" reactor wall and that initiation and termination reactions must be wall-catalyzed reactions. Thus the interpretation of the afore-mentioned data in terms of a purely homogeneous gas reaction is incorrect.…”
Section: Discussionmentioning
confidence: 99%